Bioinspired hierarchical-pore anchoring strategy advancing synergistic photocatalytic-mechanical properties. Issue 2 (April 2023) - Huang, Weizhao; Mei, Hui; Chang, Peng; Jin, Zhipeng; Bai, Shenwei; Pan, Longkai; Cheng, Laifei
Abstract: Photocatalyst with complicated 3D structures for force resistance has aroused extensive attention to solve agglomeration and recyclability, and flexible fabrication can be effectively realized by catalyst anchoring. Here, a novel MoS2 @Cu(OH)2 composite was inspired by Green Hairstreak wings for the enhanced photocatalytic and mechanical properties while the interface capacity of MoS2 was controlled after printing the bio-structural metamaterial of minimal surface. The hierarchical pore structure of the macroscopic framework, mesoscopic pore optimization and microscopic nanoneedles achieved high porosity of 81.42% and a specific surface area of up to 89.34 m 2 g −1 for abundant anchor sites. Compared with pure MoS2, the photodegradation efficiency of the MoS2 on Diamond support increased by 1.4 times because the constructed heterojunctions enhanced the separation efficiency of photogenerated electron-hole pairs. The 3D structural photocatalytic metamaterial maintained an ideal efficiency of 85.42% after recycling ten times. An ultra-high strength of 54.07 MPa was obtained from Diamond support with a modulus of 5.28 GPa. And the simulation of light irradiation proved that the minimal surface structure would not block the light path to the catalyst surface. The proposed strategy offers a new perspectivity of efficient coupling photocatalysts and minimal surface support for large-scale industrial applications. Highlights: Metamaterial support ensured light accessibility and simultaneously solved agglomeration and irrecyclability. Anchoring strategy of macro metamaterial, meso modification and micro needle constructed catalyst loading sites. The interface effect from heterojunction enhanced the separation of photogenerated electron-hole pairs.